CUSTOMS OF THE UZBEK NATION - Sharopova Muazzam Sobirjonovna (Лучшие интеллектуальные исследования, 2023)
Annotation: This article explores the rich and diverse customs of the Uzbek nation, shedding light on their cultural practices, traditions, and heritage. It provides insights into the methods used to preserve and pass on these customs, presents the results of our research, discusses their significance, and offers suggestions for their continued preservation and appreciation.